Globalisation and Gender Equality in Education: Government and NGOâ€™s Roles in Empowering Women - Jeini Usoh, Elni; Adolf Ohyver, Daniel; Puad Mat Som, Ahmad; Abu Bakar, Norsuhaily (International Journal of Engineering and Technology, 2018)
One of the remarkable advantages of globalisation is people having more access to adequate education, both for formal and informal. Although education is not shared evenly all over the world, through globalisation, there is an awakening process when most countries realise that education is not only a crucial factor in developing human resources, but also essential for economic improvement and technology expansion. Education is a primary need and a fundamental right for everyone, yet many women still lack of education, which has the potential to enhance their lives, particularly to fight against poverty. This article will argue that education needs in rural areas in Indonesia are not being shared equally by both genders. The results show that globalised standards of education are falling short for female students due to several reasons, such as financial constraints and cultural preferences for males. Therefore, the roles of the government and NGOs are vitally important in empowering women, particularly in rural areas. This article also draws the ethnographic data from rural areas in Minahasa Regency in North Sulawesi, Indonesia. This article recommended that the government should enhance the access to all educational stages, improve the education quality and distribute more funds in education to implement the educational fees exemption program. It can be concluded that NGOs can play the important role in assisting the government strategies. The roles may be conducted by embarking on campaigns for education. It may lead to increasing number of education enrolment and enlarging the opportunity for children and women to attain sufficient education.Â Â